An enhancement at the ΣK threshold (1680) MeV observed in K- p reactions at 4.2 GeV/c - Dionisi, C; Diaz, J; Armenteros, R; Gavillet, P; Gurtu, A; Hemingway, R; Mazzucato, M; Blokzijl, R; Kluyver, J; Massaro, G; Metzger, W; Schotanus, J; et al. (1978)
An enhancement in the (ΣK) mass spectrum at threshold is observed in K-p interactions at 4.2 GeV/c. It appeats both in the neutral and negative charge states. Corresponding ΛK mass distributions show weak evidence for an effect close to this threshold (∼1680 MeV). Although the interpretation of the (ΣK) enhancement by itself is ambiguous, a (ΣK)-(ΛK) coupled channel analysis gives results compatible with its interpretation as a new Ξ*. © 1978.